The Existential Unconscious: Sartre and the Dialectic of Freedom (Existential Analysis: Journal of the Society for Existential Analysis, 2017)
In conceptualising and arguing for the 'existential unconscious' in the works of Sartre, this article contends that all empirical acts of the self relate to the self's being-in-the-world as an original and a-volitional project of being. The inclusion of the unconscious makes for a dialectical approach to freedom as authenticity.
Keywords: Sartre; existentialism; unconscious; psychoanalysis; self; subjectivity; dialectic; freedom.